2008
DOI: 10.1111/j.1600-0501.2008.01537.x
|View full text |Cite
|
Sign up to set email alerts
|

Lateral ridge augmentation using particulated or block bone substitutes biocoated with rhGDF-5 and rhBMP-2: an immunohistochemical study in dogs

Abstract: Within the limits of the present study, it was concluded that both rhGDF-5 and rhBMP-2 have shown efficacy; however, their bone regenerative effect was markedly influenced by the carrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
91
2
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(107 citation statements)
references
References 43 publications
5
91
2
7
Order By: Relevance
“…Such observations might result from the different biodegradation patterns of particulated and block-type biomaterials. Some previous studies [28,29] found less biodegradation and bone formation with block bone grafts in lateral or calvarial defects. In calvarial defects that received particulated bone, new bone formation occurred on the surface of individual particles of biomaterials, and grew into the spaces between them over a longer healing period.…”
Section: Discussionmentioning
confidence: 95%
“…Such observations might result from the different biodegradation patterns of particulated and block-type biomaterials. Some previous studies [28,29] found less biodegradation and bone formation with block bone grafts in lateral or calvarial defects. In calvarial defects that received particulated bone, new bone formation occurred on the surface of individual particles of biomaterials, and grew into the spaces between them over a longer healing period.…”
Section: Discussionmentioning
confidence: 95%
“…BMP-2 and GDF-5 have been compared regarding their angiogenic and osteogenic capacity in the past [32][33][34][35]: in vitro GDF-5 not only promoted osteogenic differention of fat derived MSC but, in contrast to BMP-2, also increased vascular endothelial growth factor gene expression [35]. While the angiogenic capacity of GDF-5 was superior to BMP-2 in chick chorioallantoic membrane and rabbit cornea assays [34], the in vivo osteogenic activity of BMP-2 was higher than that of GDF-5 in calvarial defects of rats [33].…”
Section: Discussionmentioning
confidence: 99%
“…GDF-5 has also been used in mini-pig sinus augmentation, where it enhanced bone formation with a β-TCP carrier [120, 121]. In lateral ridge augmentation with a coated Bio-Oss ® block, GDF-5 resulted in increased mineralized tissue formation [122]. …”
Section: Growth Factors and Protein Deliverymentioning
confidence: 99%